Human papillomavirus vaccine beliefs and practice characteristics in rural and urban adolescent care providers - Cody L. Goessl; Ben Christianson; Kayla E. Hanson; Elizabeth J. Polter; Scott C. Olson; Thomas G. Boyce; Denise Dunn; Charnetta L. Williams; Edward A. Belongia; Huong Q. McLean; Jeffrey J. VanWormer (BMC, 2022)
Abstract Background The human papillomavirus (HPV) vaccine is recommended for all adolescents age 11-12 years. HPV vaccine coverage remains suboptimal in the United States though, particularly in rural areas. We surveyed adolescent immunization providers in two Midwestern states to assess rural vs. urban differences in HPV vaccine resources, practices, and attitudes. Methods A cross-sectional survey was sent to all licensed adolescent care providers in a subset of urban and rural counties in Minnesota and Wisconsin during 2019. Multivariable regression was used to identify attitudes and practices that differentiated rural vs. urban providers. Results There were 437 survey respondents (31% rural). Significantly fewer rural providers had evening/weekend adolescent vaccination appointments available (adjusted odds ratio (aOR) = 0.21 [95% confidence interval (CI): 0.12, 0.36]), had prior experience with adolescent vaccine quality improvement projects (aOR = 0.52 [95% CI: 0.28, 0.98]), and routinely recommended HPV vaccine during urgent/acute care visits (aOR = 0.37 [95% CI: 0.18, 0.79]). Significantly more rural providers had standing orders to administer all recommended adolescent vaccines (aOR = 2.81 [95% CI: 1.61, 4.91]) and reported giving HPV vaccine information to their patients/families before it is due (aOR = 3.10 [95% CI: 1.68, 5.71]). Conclusions Rural vs. urban differences in provider practices were mixed in that rural providers do not implement some practices that may promote HPV vaccination, but do implement other practices that promote HPV vaccination. It remains unclear how the observed differences would affect HPV vaccine attitudes or adolescent vaccination decisions for parents in rural areas.